2020
DOI: 10.3390/antiox9020103
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory and Antioxidant Activity of Pollen Extract Collected by Scaptotrigona affinis postica: in silico, in vitro, and in vivo Studies

Abstract: Bees are of great importance for plant diversity for being an important pollinating agents. Stingless bees such as Scaptotrigona affinis postica, is cultivated largely due to the products offered by it. Pollen is one of these products, which has been highlighted for exhibit various therapeutic properties. Considering the bioactivity of this natural product, this study investigated the antioxidant, anti-inflammatory, antinociceptive activities, and elucidated the chemical composition of pollen collected extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 42 publications
1
29
0
Order By: Relevance
“…Honey bees ( Apis Mellifera ) harvest the pollen from plant flowers and enrich it with salivary enzymes and nectar [ 1 ] to obtain small granular-looking grains (bee pollen) that are transported into the apiary. Bee pollen is abundant and essential nourishment that could satisfy the protein needs of the entire colony [ 2 , 3 ]. A single pollen bead has a color that is due to its specific botanical origin.…”
Section: Introductionmentioning
confidence: 99%
“…Honey bees ( Apis Mellifera ) harvest the pollen from plant flowers and enrich it with salivary enzymes and nectar [ 1 ] to obtain small granular-looking grains (bee pollen) that are transported into the apiary. Bee pollen is abundant and essential nourishment that could satisfy the protein needs of the entire colony [ 2 , 3 ]. A single pollen bead has a color that is due to its specific botanical origin.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it has been explored for its ability to remove free radicals. Its antioxidant activity using in vitro study has been documented in Malaysia [ 79 , 99 , 113 ], Brazil [ 47 , 105 , 106 ], Venezuela [ 9 , 84 ], and Australia [ 100 ].…”
Section: Health Benefitsmentioning
confidence: 99%
“…Barbara et al reported desirable nutritional properties for bee pollen extracts collected from stingless bees [ 130 ]. These extracts were reported to contain polyphenols, flavonoids and fatty acids, suggesting the antioxidant potential of stingless bee pollen [ 126 , 130 ]. These findings have been supported by a recent study on eight stingless bee pollen samples from different regions in the Philippines [ 127 ].…”
Section: Stingless Bee Pollenmentioning
confidence: 99%
“…Another study has shown stingless bee pollen extracts have anti-inflammatory effects by reducing mouse footpad edema and also decreasing evidence of a pain (antinociceptive) response following administration of acetic acid [ 130 ]. A recent study suggested that the anti-inflammatory effect of stingless bee pollen results from its antioxidant activity that inhibits cyclooxygenase (COX), which promotes inflammation by producing prostaglandins [ 126 ]. Furthermore, a study to detect the synergistic effect of stingless bee pollen extracts with cisplatin (a chemotherapeutic drug) on breast cancer cells showed antioxidant and antiproliferative effects of bee pollen against the cancer cells [ 129 ].…”
Section: Stingless Bee Pollenmentioning
confidence: 99%